The Use of Financial Literacy and Lifestyle Media for Financial Management of Students of the Faculty of Teacher Training and Education, University of Muhammadiyah - Istighfaris Rezki (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: The development of the digital era has transformed student financial management patterns, particularly in the use of financial literacy media and lifestyle development. As future educators, students at the Faculty of Teacher Training and Education are required to possess sound and responsible financial management skills. Aim: This study aims to analyze the influence of the use of financial literacy and lifestyle media on the financial management of FKIP students at Muhammadiyah University. Method: The study employed a quantitative approach with a causal associative design. The study population consisted of 439 students, with a sample of 148 respondents selected using probability sampling techniques. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regression. Result and Disscusions: The results showed that the use of financial literacy media had a positive and significant effect on student financial management. Meanwhile, lifestyle had a significant negative effect, indicating that a tendency toward a consumptive lifestyle decreases the quality of financial management. Simultaneously, the use of financial literacy media and lifestyle significantly influenced student financial management, contributing 49.3%. These findings underscore the importance of improving financial literacy and lifestyle management to foster healthy and sustainable student financial behavior.